2022
DOI: 10.3233/thc-thc228034
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of skeletal myogenesis in C2C12 cells through modulation of Pax7, MyoD, and myogenin via different low-frequency electromagnetic field energies

Abstract: BACKGROUND: A low-frequency electromagnetic field (LF-EMF) exerts important biological effects on the human body. OBJECTIVE: We previously studied the immunity and atrophy of gastrocnemius muscles in rats with spinal cord injuries and found that LF-EMF with a magnetic flux density of 1.5 mT exerted excellent therapeutic and preventive effects on reducing myotubes and increasing spatium intermusculare. However, the effects of LF-EMF on all stages of skeletal myogenesis, such as activation, proliferation, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Further, we demonstrated that C2C12 on fungal carriers expressed key markers of myogenesis in response to media-induced differentiation. MYOD1 , MYOG , and MYH are myogenic regulatory factors that regulate the development of functional embryonic skeletal fiber muscle differentiation 40 , 41 . MYH1 and MYH2 are genes that encode MyHC-2X and MyHC-2A, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we demonstrated that C2C12 on fungal carriers expressed key markers of myogenesis in response to media-induced differentiation. MYOD1 , MYOG , and MYH are myogenic regulatory factors that regulate the development of functional embryonic skeletal fiber muscle differentiation 40 , 41 . MYH1 and MYH2 are genes that encode MyHC-2X and MyHC-2A, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the C2C12 cell line provides an invaluable tool to study the molecular biology and mechanisms of myogenic regulation [43,44], muscle differentiation [45], regeneration, and muscle atrophy [41].…”
Section: C2c12 Cell Linementioning
confidence: 99%
“…PEMF has been shown to increase the myotube diameter and fusion index, activating TRPC1-mediated calcium entry and mitochondrial respiration downstream of calcineurin-dependent transcriptional regulation and P300/CBP-associated factor (PCAF)-epigenetic signaling, which was previously found to be involved in myogenesis [19,20]. Even less is known about the ability of PEMF to accelerate human SkMC regeneration after injury or the chemical mechanism behind this effect [20][21][22]. Here, we studied the potentiality of PEMF to stimulate the early regeneration of human SkMC.…”
Section: Introductionmentioning
confidence: 99%